An Experimental Study on Strength of Concrete Due To Cold Joints - Banstola, Prabin; Ligal, Dipesh; Timalsina, Hare Ram; Baral, Nirmal Prasad (Journal of Advanced Research in Geo Sciences & Remote Sensing; Vol 8 No 3&4 (2021): Journal of Advanced Research in Geo Sciences & Remote Sensing, 2022)
In major infrastructure projects with huge concreting works, concreting works cannot be completed in a single day. Concreting works for infrastructures like major bridges, dams are done in intervals of days and weeks when concreting are done in large volume. It is not possible to complete mass concreting in a single day due to limitation of labor, unavailability of sufficient equipment, labor productivity and site conditions which leads to the formation cold joints. This study focuses primarily on by what means the strength of concrete is affected from cold joints formation and how the effect of such joints can be improved in the construction site. This study shows the variation of strength of concrete with various types of joints formed during placing of concrete. Compressive strength and Split tensile strength of concrete were observed during the test. It was found that the presence of joint reduced both the compressive strength and split tensile strength of concrete. The compressive strength of concrete was found to decrease by 22-25% in the case of cubes with joints while the split tensile strength decreased by 23%. The study also focused on the use of cement slurry (1:1) and chemical admixture on the cold joints and found that use of cement slurry reduced the loss in compressive strength by 30.80% in case of concrete with vertical joints and 13.82% in case of split tensile strength of cylinder. Chemical admixture also showed improvement in compressive strength by 21.50% and split tensile strength by 17.51%. However, improvement in compressive strength of concrete with horizontal joints with the use of chemical admixture or cement slurry didn’t show satisfactory results. This study recommends surface treatment of cold joints with cement slurry or chemical admixture when concreting in large volume to avoid the effects of cold joints. How to cite this article:  Ligal D, Baral NP, Timalsina HR et al. An Experimental Study on Strength of Concrete Due To Cold Joints. J Adv Res Geo Sci Rem Sens 2021; 8(3&4): 1-7. DOI: https://doi.org/10.24321/2455.3190.202104